The separation of the Kurdistan Region of Iraq from the Iraqi state as one way to solve the problem (Analytical study in the light of international and internal law) - شاری خالد معروف (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
In this research which is tilted “To what extent can the Kurdistan Region separate from Iraq”. As a solution for its problems. We discussed the term of “Separation” and its types based on the local and international legal texts. After that we shed light on the legal, political, and economic factors that pushes Kurdistan to separate from the federal State of Iraq, and then we discussed the referendum as a peaceful mechanism that is accepted by legal and democratic principles to reach the goal of independence to solve all the problems between the region and the federal state of Iraq. The research also contains a legal evaluation to hold a referendum as a tool to gain independence according to local and international laws in order to solve problems that affect the Kurdistan region.